From informal microfinance to linkage banking: putting theory into practice, and practice into theory - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2007)
Academic research generates scholarly publications which practitioners do not read. Practitio-ners face challenges which scholars do not address. They speak different languages and move in different worlds. In a field now known as microfinance, this paper is a personal account of taking turns living in both worlds - each a microcosm of its own-, and bridging the gap between theory and practice. The author describes how the journey took him through paradigm shifts and terminology changes, through history and regions, and by doing so illustrates the complexity of interventions and timing, and the importance of the interaction between theory and practice.
Keywords: 330; Mikrofinanzierung; Informeller Finanzsektor; Bankgeschäft; Theorie-Praxis-Problem; Theorie; Entwicklungsländer